Analisis Produktivitas Tenaga Kerja Dengan Metode Field Ratings (Studi Kasus: Pekerjaan Penulangan Pelat Di Proyek Gedung Sudirman Place Jakarta Lantai 1) - Delta Perkasa (NUCLEUS, 2022)
This research is on the activity of each worker at a certain time in plate reinforcement work. The slab reinforcement is the same type from zone I to zone XIV. Each zone has an area of ??8.4x8.4 m2. The plate reinforcement workers consist of 2 groups. Group A consisted of 10 people working from zone I to zone VII for 6 days. Group B consisted of 10 people working on zone VIII to XIV for 6 days. Based on the results of research using the field ratings method, it is known that the average (mean) percent effective time of Group A workers on the 1st to 4th day is 68.72%, the 5th day is 69.02% and the 6th day is 69.06 %. Meanwhile, Group B on the 1st to 2nd day was 68.80%, the 3rd and 4th day was 68.83%, the 5th and 6th day was 68.93%. The total working time for 6 days carried out by workers on the installation of floor slab reinforcement is 540 minutes/person, the average (mean) total effective time of Group A workers is 371.67 minutes/person (68.83%) and the average (mean) ) the total effective time for Group B workers is 371.80 minutes/person (68.85%). So the average (mean) level of labor productivity in Groups A and B for 6 days is satisfactory or effective because the percent of effective time is above 60%. Keywords: Productivity, Labor, Plate Reinforcement, Field Ratings